ENGAGING STUDENTS IN A FLIPPED CLASSROOM INSTRUCTION: TEACHING ENGLISH FOR SPECIFIC PURPOSE (ESP) IN HIGHER EDUCATION - Al Baekani, Abdul Kodir; Hapsari, Nesti; Muslihat, Asep (University of Kuningan, 2023)
ESP (English for Specific Purpose) is part of ELT (English Language Teaching) which contains the teaching of English as a foreign language. Every English teacher, especially ESP, must innovate in the delivery of their teaching materials which are always carried out from year to year. This study reports on the perceptions of economics major students about the use of flipped classroom models in learning English for Specific Purpose (ESP). Illustrated in classroom action research through reflective journals, photo elicitation and interviews data. Qualitative findings show that: 1) all students enjoy watching video teaching materials and have an interest in using them to learn English; 2) the use of flipped classroom in learning English makes students independent and active in learning English; 3) flipped classroom engaged students in learning English in different contexts of discourse; 4) flipped classroom mode motivated students in learning English. The findings of this study are expected to be useful for other researchers interested in EFL learning innovations or teachers who are looking for teaching English for Specific Purpose (ESP).